Type 2 Diabetes: An Emerging Pediatric Disease - Dhillon, Gurmohan; Berger, Robert (DALHOUSIE MEDICAL JOURNAL, 2005)
Since the early 1990s, clinicians have recognized a rising incidence of Type 2 diabetes in youth and adolescents. The rising incidence of diabetes has been directly correlated with the increasing incidence of obesity in children with BMI ranging from 26-38 kg/m2. This phenomenon has been observed worldwide including parts of Europe and Asia. Lifestyle changes related to behavioral, environmental and social factors have been suggested as contributing to increasing childhood obesity and Type 2 diabetes. Genetics is also thought to be influencing this trend, as parental obesity and a family history of diabetes appears to put children at higher risk for these diseases. The American Diabetes Association has provided strong recommendations regarding treatment of Type 2 diabetes in youth. Initial management should focus on diet modification and increasing physical activity. Pharmacological therapy for controlling glucose levels, hypertension and hyperlipidemia is recommended if necessary. The strongest recommendation in the literature focuses on disease prevention as youth diagnosed with Type 2 diabetes will be at higher risk for cardiovascular disease and diabetic complications at a young age. Prevention strategies are designed to address both family-based and school-based programs. These programs emphasize physical activity, appropriate dietary choices, behavior modification and parental involvement.